Ukraine War as a Cause of Food Crisis: A Framing Analysis of Three Giant International Media - Intan Tiara Kartika; Ali Maksum (Ikatan Sarjana Komunikasi Indonesia, 2023)
Food availability is one of the important things that any state must fulfill so that its people can live healthy and active lives. Currently, the world is encountered with food insecurity that threatens human welfare. The world, which has not yet recovered from the domino effects of climate change, the COVID-19 pandemic, and most recently the Russia-Ukraine war, is becoming increasingly unprepared for a global food crisis. Malnutrition, mass starvation, and famine will become major problems if this crisis continues. Warnings on a global food crisis that are often ignored have put the global food system on the verge of collapse. With the increasing level of hunger, the issue of food crisis has become a hot topic of discussion again. Foreign media are competing to report on the food crisis particularly the causes of the rapidly developing food crisis. The purpose of this study is to find out how the media has framed the causes of the food crisis. This study will take samples from three major regional media, namely Al Jazeera, Asia Times, and Washington Post, during the period of April 2020 to June 2022. This research applies a qualitative research method using the content of foreign news. The data was processed using the N Vivo 12 Plus and analyzed using media framing theory and food insecurity. The findings of this study show that the issue of war between Russia and Ukraine is the most widely used form of framing by the three media. This is because the war disrupts not only world food production but also food distribution. This research is expected to be developed using more news samples to get more varied results.